Peningkatan Keterampilan Pembuatan Sabun dan Lulur oleh Kelompok Budidaya Rumput Laut - Tuti Handayani Zainal; Maria Ulfa Maria; Ruqayyah Jamaludddin; Nur Azmi; Risky Saldy (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: Seaweed possesses substantial potential but remains under-processed and underutilized. One of the products derived from seaweed is soap and body scrub. This community service activity aims to increase public understanding of seaweed, stimulate creative ideas, and equip participants with the basic skills for manufacturing seaweed-based products. Methodology/approach: The partner for this community service is the Pelita Makkio Baji Seaweed Cultivation Group in Ujung Baji Village, Takalar District, which involves 15 participants. The activity was conducted through training and mentoring in the production of soap and body scrub products. The participants’ understanding was measured through pre-tests and post-tests Results/findings: The pre-test indicated that the community’s knowledge of the benefits and innovations of seaweed was approximately 20 %, and after the activity (post-test), it reached 100 %. This activity also led to the creation of social media accounts as a marketing medium. Conclusions: Based on the above results, it can be concluded that community service activities have a significant positive impact on the community’s knowledge. Limitations: This study involved only a small number of participants from a single village; thus, the findings may not be generalizable to the wider community. Further activities involving more diverse groups and locations are recommended to strengthen the results Contributions: This program contributes to community empowerment by enhancing the ability of local seaweed farmers to innovate and manufacture seaweed-based products. It also provides a practical example of sustainable economic development through local resource utilization.